Influence of contextual factors on physical demands and technical-tactical actions regarding playing position in professional soccer players - Díez, A.; Lozano, D.; Arjol-Serrano, J. L.; Mainer-Pardos, E.; Castillo, D.; Torrontegui-Duarte, M.; Nobari, H.; Jaén-Carrillo, D.; Lampre, M. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background The aim of this study was to analyse the physical demands and technical-tactical actions for each playing position according to game location and final outcome in professional soccer players.